Inflation Determinants in Paraguay : Cost Push versus Demand Pull Factors - Monfort, Brieuc; Pena, Santiago (Washington, D.C. : International Monetary Fund, 2008)
This article uses two analytical methodologies to understand the dynamics of inflation in Paraguay, the mark-up theory of inflation and the monetary theory of inflation. We also study the impact of different monetary aggregates. The results suggest that monetary factors, in particular currency in circulation, play a major role in determining long-run inflation, while foreign prices, in particular from Brazil, or some food products have a large impact on the short-term dynamics of inflation. Wage indexation may also contribute to locking up price increases.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet